2015
DOI: 10.2527/jas.2015-9515
|View full text |Cite
|
Sign up to set email alerts
|

Effects of breed, sex, and concentrate supplementation on digestibility, enteric methane emissions, and nitrogen utilization efficiency in growing lambs offered fresh grass1

Abstract: Forty-eight lowland lambs were used in a completely randomized design (23-d period) with a factorial arrangement of treatments: 2 breeds (Highlander vs. Texel) × 3 sexes (female vs. intact male vs. wether) × 2 diets (fresh grass vs. fresh grass plus 0.5 kg/d pelleted concentrate). Animals ( = 48) were approximately 5 mo old and 36 ± 5.0 kg BW at the commencement of the study with 4 lambs for each breed-sex-diet combination. Fresh grass was harvested daily from the first regrowth of perennial ryegrass sward and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…The N utilization efficiency can be improved by formulating balanced diets that supply sufficient fermentable energy for rumen microbes to capture ammonia for protein synthesis ( Dijkstra et al, 2011 ). It was observed that the concentrate supplementation was an effective way to improve microbial protein synthesis and shift N excretion from urine to feces ( Islam et al, 2000 ; Zhao et al, 2015 ). However, in the present study, feeding concentrates at 0.5 kg/d had no significant effects on N utilization efficiency in terms of N excretion or retained N as a proportion of N intake.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The N utilization efficiency can be improved by formulating balanced diets that supply sufficient fermentable energy for rumen microbes to capture ammonia for protein synthesis ( Dijkstra et al, 2011 ). It was observed that the concentrate supplementation was an effective way to improve microbial protein synthesis and shift N excretion from urine to feces ( Islam et al, 2000 ; Zhao et al, 2015 ). However, in the present study, feeding concentrates at 0.5 kg/d had no significant effects on N utilization efficiency in terms of N excretion or retained N as a proportion of N intake.…”
Section: Discussionmentioning
confidence: 99%
“…Each treatment had four lambs and were balanced within each breed for animal age and live weight. The sheep were housed in individual pens for 19 d, then transferred to individual crates that were placed in climate-controlled open circuit respiration chambers (one sheep per crate per chamber) and remained there for 5 d with nutrient digestibility and CH 4 emissions measured during the final 4 d. All equipment, sampling procedures, analytical methods, and calibrate of chambers were described by Zhao et al (2015) . Water was freely available during the period of study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ruminants are the largest source of methane emissions among livestock, releasing methane into the atmosphere through eructation. Methane production from ruminants is influenced by numerous factors, including diet, breed, genetics, and geographical range, which may have interactive effects on methane emission ( Basarab et al, 2013 ; Carberry et al, 2014 ; Henderson et al, 2015 ; Zhao et al, 2015 ; Roehe et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our results are in concurrence with the previous reports of McGuire et al (2013), Kang et al (2015), who reported that increasing levels of dietary CP in ruminants increased the N intake and N-retention than those fed low dietary CP levels. Islam et al (2000) and Zhao et al (2015) also observed that concentrate supplementation was an effective way to improve rumen microbial protein synthesis and shift N excretion from urine to faeces. It has been well established that the N utilization efficiency can be improved through balanced diet that can synchronously supply adequate fermentable energy and N for maximum microbial growth in the rumen and capture ammonia for protein synthesis (Dijkstra et al 2011).…”
Section: Nitrogen Balancementioning
confidence: 94%